The Implementation of Project-based Learning in English Classrooms: A Case Study at SMKN 1 Mataram - Irma Rizki Utami; Ahmad Zamzam; Lalu Jaswadi Putera (Jurnal Ilmiah Profesi Pendidikan, 2026)
This research examined the implementation of Project-based Learning (PjBL) in English classes at SMKN 1 Mataram. The study aimed to examine students’ engagement, autonomy, and attitudes during project activities, analyse the relationship between PjBL and constructivist learning in vocational education, and provide insights for teacher training, curriculum development, and classroom practices in Indonesian vocational schools. This study used a qualitative case study design involving one class, Class XII LPS 1 majoring Layanan Perbankan Syariah (Sharia Banking Service), consisting of 1 English teacher and 28 students selected through purposive sampling technique. The data collection was employed through observation checklists, document analysis, and field notes, with validated instruments to ensure credibility. The data analysis was conducted thematically to identify patterns in the implementation of PjBL. The findings showed that the implementation of PjBL varied across two observed meetings and remained incomplete. In the first meeting, the teacher only implemented the initial stage by introducing essential questions related to job interviews. Student participation was limited, and no further stages such as project planning or development were conducted. The teacher also shared a personal experience of being rejected for a job in Belgium because she wore a hijab to engage students in discussion. In the second meeting, the implementation improved as the teacher facilitated group work, introduced a project, and monitored students’ activities. However, important stages such as detailed planning, presentation, assessment, and reflection were still absent. Although some progress was evident, the implementation did not represent the complete cycle of PjBL and failed to fully support constructivist principles or student autonomy. The study concludes that comprehensive teacher training, structured planning, and the implementation of all PjBL stages are necessary to maximize its effectiveness in vocational English classrooms.